Synthesis and Structural Studies of Complexes of Co(II), Ni(II), Cu(II), Zn(II) and Pd(II) with Semi- and Thiosemicarbazones - Rama Chary, M.; Sudershan, T.; Laxma Reddy, K.; Srihari, S. (Asian Journal of Chemistry, 2012)
Complexes of Co(II), Ni(II), Cu(II), Zn(II) and Pd(II) with semicarbazone and thioxemicarbanone of 2,4-dihydroxyacetophenone have been prepared and characterized by analytical, conductivity, magnetic, thermal and IR, UV-vis and ESR spectral data. The ligands with all the metals form complexes of the type ML2 (M = metal; L = ligand) which are found to be non-electrolytes in DMF. IR data indicate that the ligands act, in the case of Co(II), Ni(II), and Cu(II), as mononegative, tridentate ones – semicarbazone coordinating through O, N & O and thiosemicarbazone through O, N & S. However, they show mono-negative, bidentate nature towards Zn(II) and Pd(II) binding through oxygen of o-hydroxy group and nitrogen of azomethine group.